DIGITAL MONITORING AND MANAGEMENT STRATEGIES IN THE PREVENTION OF OPIOID INTOXICATION - Monteiro, Santiago Bailona; Honório , Ana Karoline Souza; Miranda, Isabella De Souza; Santana , Ianca Gontijo Cavalcante (CIPEEX, 2025)
Introduction: Opioid intoxication remains a major challenge for healthcare systems, with a significant impact on morbidity and mortality, especially among chronic users and young adults. In this context, digital technologies and public health management strategies emerge as promising tools for prevention and early intervention. Objective: To analyze the role of digital technologies and public health management strategies in preventing and monitoring opioid intoxication, highlighting innovative approaches and their potential integration into public policies. Methodology: A bibliographic review was conducted between August 2024 and May 2025, using the BVS, SciELO, LILACS, and PubMed databases. The descriptors “opioid intoxication,” “naloxone,” “health technologies,” and “public health management” were applied in both Portuguese and English. Results and discussion: The studies reviewed indicate that digital monitoring systems, including mobile applications and wearable sensors, show potential for early detection of intoxication signs. The use of pulse oximetry sensors integrated with mobile devices enables remote monitoring and automatic alerts. Moreover, programs combining naloxone distribution with digital alert systems have been associated with reduced mortality rates. However, integrating these technologies into public health services still faces challenges related to infrastructure, professional training, and data privacy. Policies that incorporate digital monitoring, naloxone training, and harm reduction strategies have shown particularly promising outcomes. Conclusion: Digital monitoring, combined with integrated management strategies, represents a valuable tool in the prevention of opioid intoxication. Its effective implementation requires coordinated policies and investment in technological infrastructure, with the potential to reduce morbidity and mortality associated with opioid misuse.